The Impact of the Digital Economy Development on the Organizational Structure of the Company - Safarov B.; Batirov J. A. (International Journal on Integrated Education, 2022)
This article discusses the process of formation of the concept of "digital economy" in a term of scientific terminology, particularly in Uzbekistan. The main prerequisites for the development of digitalization of the economy and its impact on the business process of enterprises are identified. This approach involves not only the installation of modern hardware or software, but also fundamental changes in management approaches. As a result, there is an increase in the productivity of each employee and the level of customer satisfaction that can be achieved through the use of advanced digital technologies in the production process of goods or services.